A method of DC short-circuit analysis and thyristor determination for high power nuclear fusion converter. (November 2022) - Wang, Zhongma; Shi, Chaoyi; Gao, Xianhe; Zhang, Sheng; Huang, Liansheng
Abstract: In the design of fusion power supply, the DC side fault analysis and the thyristor determination of converter is a very important step. In this paper, to improve the accuracy of fault current prediction and reduce the waste of device selection, the equivalent impedance method of the converter system is proposed to calculate the converter fault current, and then the formula of steady and transient parameters of thyristor is proposed. The equivalent impedance model is established for typical faults of converter, and the calculated fault current is compared with the simulation result. Finally, the style and number of thyristors in parallel is determined by the consideration of junction temperature and fault current thermal accumulation in short time ( I 2 t ).